A TANGGAPAN FISIOLOGIS DAN HASIL EMPAT KULTIVAR PADI GOGO LOKAL SULAWESI TENGAH TERHADAP CEKAMAN KEKERINGAN - Boy, Ruslan; Indra Dewa, Didik; Susila Putra, Eka Tarwaca; Kurniasih, Budiastuti (BPFP Universitas Bengkulu, 2022)
[PHYSIOLOGICAL RESPONSES AND YIELDS OF FOUR LOCAL GOGO RICE CULTIVARS OF CENTRAL SULAWESI TO DROUGHT STRESS]. Rice is the most important staple food for Indonesians and can be grown in dry land agroecosystems as an upland rice. The research was conducted to study the physiological mechanisms related to drought resistant schemes on four local upland rice cultivars of Central Sulawesi. Field research was carried out using factorial Completely Randomized Block Design (CRBD) with two factors and three blocks as replication. The first factor was four cultivars of upland rice, i.e., Habo, Hiwanggu, Sunggul, and Lambara; while watering intervals of once in one, two, four and eight days was considered as second factor. The observed variables of this experiment were soil moisture, relative water content of leaf, stomatal conductance, concentration of leaf carbon dioxide, transpiration rate, photosynthesis rate, and yield of grain per grove. The collected data were analyzed with regression using independent variables of soil moisture and dependent variables of relative water content on leaf, stomatal conductance, concentration of carbon dioxide on leaf, transpiration rate, photosynthesis rate and yield of grain per grove. The relationship among observed variables was determined using correlation analysis. The results showed that drought resistant upland rice cultivars (Habo and Sunggul) required less optimum soil moisture than those of non-drought resistant cultivars (Hiwanggu and Lambara) to maximize relative water content, stomatal conductance, carbon dioxide, transpiration rate and photosynthesis rate. Soil moisture contributions to maximum yield of grain per grove on Habo, Sunggul, Hiwanggu and Lambara cultivars were 23.41%, 23.00%, 27.14% and 26.67%, respectively.